Hematopoietic stem cell transplantation: an Italian monocentric experience on the health assessment and eligibility of adult-related donors - Valentini, Caterina Giovanna; Ceglie, Sara; Fatone, Federica; Metafuni, Elisabetta; Pellegrino, Claudio; Chiusolo, Patrizia; Sica, Simona; Teofili, Luciana (Frontiers in Oncology, 2024)
Indications for HSCT are increasing worldwide, paralleled by a growing demand for donors of therapeutic cells. Herein we report our real-world experience of adult HPC donor assessment during a 5-year study period (2018-2023): we have retrospectively revised data of 455 potential related stem cell donors, consecutively evaluated at our center. Donor medical history was assessed by a questionnaire and an interview with a trained physician experienced in donation procedures, to evaluate donor fitness and medical history. Pre-existing health disorders were fully investigated. Behavioral risk factors for communicable infectious diseases were also routinely explored. Overall, 351 donors were finally assessed as eligible for HPC donation and 233 underwent stem cell collection, 158 through apheresis from mobilized peripheral blood, and 75 through bone marrow harvest. Among them, 27 donors were selected despite the presence of pre-existing health conditions, that would be potential exclusion criteria for unrelated donors: 16 suffered from well-controlled cardiovascular diseases (CVD), and 11 from allergic diathesis. Most of the selected donors with pre-existing disorders were candidates for apheresis HPC collection (21, 77.8%), while only 6 (22.2%) underwent BM harvest. We then analyzed the data relative to the corresponding 233 allogeneic HSCT to explore if the presence of pre-existing diseases in the donors could show any association with transplant characteristics. Transplants from CVD and allergy donors showed no significant disparities in comparison with those from healthy donors. A significant difference emerged regarding the disease severity, with a higher proportion of patients with high/very high disease risk index (DRI) among those receiving grafts from CVD donors (68.7% in transplants from CVD donors versus 36.0% in transplants from healthy donors, p=0.005).Multivariate analysis confirmed that high/very high DRI patients had an increased probability of receiving donations from CVD donors (OR 4.89, 95%CI 1.15-20.86, p=0.031). Among donors with well-controlled pre-existing conditions, no adverse events were recorded during stem cell collection nor at follow-up. Our results suggest that in patients at high risk for relapse requiring a prompt allogeneic transplant, a familiar donor might be accepted for HPC apheresis donation on less strict criteria than unrelated donors, without risk for both donor and patient.